Nanographene oxide-based radioimmunoconstructs for in vivo targeting and SPECT imaging of HER2-positive tumors. - Cornelissen, B; Able, S; Kersemans, B; Waghorn, P; Myhra, S; Jurkshat, K; Crossley, A; Vallis, K (Elsevier, 2013)
Nanographene oxide (NGO) is a novel nano-wall material that tracks to tumors in vivo, and which, as a consequence of its large surface area, has the capacity to carry a large payload. This study explores the use of anti-HER2 antibody (trastuzumab)-conjugated NGO, radiolabeled with (111)In-benzyl-diethylenetriaminepentaacetic acid (BnDTPA) via ππ-stacking, for functional imaging. In two HER2-overexpressing murine models of human breast cancer, high tumor-to-muscle ratio was achieved, resulting in clear visualization of tumor using single-photon emission computed tomography (SPECT). In the BALB/neuT model and in BALB/c nu/nu mice bearing 231/H2N xenografts, tumor accumulation amounted to 12.7 ± 0.67 and 15.0 ± 3.7% of the injected dose/g (%ID/g) of tumor tissue at 72 h, with tumor-to-muscle ratios of 35:1 and 7:1, respectively. Radiolabeled NGO-trastuzumab conjugates demonstrated superior pharmacokinetics compared to radiolabeled trastuzumab without NGO, with more rapid clearance from the circulation. The use of NGO as a scaffold to build radiolabeled nano-immunoconstructs holds promise for molecular imaging of tumors.